First 1000 Days of Life Education for Cadres at the Work Area Health Center in Sambikerep District, Surabaya - Melina Sari; Dian Shofiya; Ani Intiyati; Taufiqurrahman; Nur Hatijah; Nuning Marina Pengge; Juliana Christyaningsih; Devi Eka Ratnasari; Atika Nuswantari; Mujayanto; Erlyna Jayeng Wijayanti; Khristine Saputri (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The First 1000 Days of Life Movement (HPK) is also known as Scaling Up Nutrition (SUN) as a state effort to accelerate nutrition improvement, especially handling nutrition from 1000 days from pregnancy to two years of age. Pregnant women, nursing mothers, newborns and children under two years of age (baduta) are the target groups to improve the quality of life for the first 1000 days of humanity. For cadres as the spearhead of health workers who are directly involved with the community, there is still a low level of knowledge of cadres from an academic and technical perspective regarding the implementation of Posyandu. Providing 1000 HPK education is expected to be able to carry out posyandu activities optimally on target. The 1000 HPK cadre education activities showed an increase in scores for general knowledge of posyandu cadres, attitudes and actions of cadres and knowledge of balanced nutrition. The knowledge that the respondents had before being given education & training was good, this is probably due to the age characteristics that are in the range of 30-40 and the education of the respondents who graduated from high school allows the respondents to have good knowledge.